Developing an Enzyme-Assisted Derivatization Method for Analysis of C27 Bile Alcohols and Acids by Electrospray Ionization-Mass Spectrometry - Eylan Yutuc (Molecules, 2019)
Enzyme-assisted derivatization for sterol analysis (EADSA) is a technology designed to enhance sensitivity and specificity for sterol analysis using electrospray ionization–mass spectrometry. To date it has only been exploited on sterols with a 3β-hydroxy-5-ene or 3β-hydroxy-5α-hydrogen structure, using bacterial cholesterol oxidase enzyme to convert the 3β-hydroxy group to a 3-oxo group for subsequent derivatization with the positively charged Girard hydrazine reagents, or on substrates with a native oxo group. Here we describe an extension of the technology by substituting 3α-hydroxysteroid dehydrogenase (3α-HSD) for cholesterol oxidase, making the method applicable to sterols with a 3α-hydroxy-5β-hydrogen structure. The 3α-HSD enzyme works efficiently on bile alcohols and bile acids with this stereochemistry. However, as found by others, derivatization of the resultant 3-oxo group with a hydrazine reagent does not go to completion in the absence of a conjugating double bond in the sterol structure. Nevertheless, Girard P derivatives of bile alcohols and C27 acids give an intense molecular ion ([M]+) upon electrospray ionization and informative fragmentation spectra. The method shows promise for analysis of bile alcohols and 3α-hydroxy-5β-C27-acids, enhancing the range of sterols that can be analyzed at high sensitivity in sterolomic studies.